Analisis Pengendalian Persediaan Bahan Baku Asphalt Mixing Plant (AMP) Menggunakan Model Economic Order Quantity dan Period Order Quantity - Khoiri, Fitri; Chairunisah, Chairunisah (Griya Journal of Mathematics Education and Application, 2025)
This research analyzes raw material inventory control at PT. Adhi Karya (Persero) Tbk AMP Medan Area, considering warehouse capacity limitations and demand fluctuations. The study employs the Economic Order Quantity (EOQ) and Period Order Quantity (POQ) models to determine optimal order quantity, ordering frequency, and total inventory costs. Results show that both models yield substantial cost efficiencies compared to the company’s current policy. The total inventory cost using the EOQ model is Rp630,499,314.50, while the POQ model results in Rp626,289,722.53. In contrast, the company’s current approach incurs a total cost of Rp1,648,260,123.80. Consequently, EOQ and POQ generate savings of Rp1,017,760,809.30 and Rp1,021,970,401.27 respectively. These findings indicate that both models offer effective and economical solutions for inventory control. Additionally, they help avoid overstock and stockouts while adapting to production demands and limited storage space, thus optimizing procurement strategies.